Digitales Verwalten - Digitales Archivieren. 8. Tagung des Arbeitskreises ,,Archivierung von Unterlagen aus digitalen Systemen am 27. und 28. April 2004 im Staatsarchiv Hamburg" - Hering, Rainer; Schäfer, Udo; der Freien und Hansestadt Hamburg, Staatsarchiv (Veröffentlichungen aus dem Staatsarchiv der Freien und Hansestadt Hamburg, 2004)
Digital storage of information is becoming increasingly important in public and private administration. Archives must therefore participate at an early stage in the implementation of content management systems in order to be able to pass on historically valuable digital documents to future generations in an authentic form. The eighth conference of the working group "Archiving of documents from digital systems" was organised by the Hamburg State Archives on 27 and 28 April 2004 under the title "Digital administration - digital archiving". It includes archivists from state and municipal archives, business and church archives in Germany, Austria and Switzerland. The archival handling of digital documents, the preservation of authenticity and the long-term storage of electronic signatures are the defining themes of the 16 contributions documented in this volume.